2015
DOI: 10.1182/blood-2015-03-634329
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic agents of broad applicability produced by selective tuning of factor Xa zymogenicity

Abstract: Key Points Modulation of FX(a) zymogenicity yields proteins with a broad range of half-lives and biologic function yet potent in vivo efficacy. Zymogen-like variants are attractive molecules for alleviating bleeding in different clinical scenarios such as hemophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In vitro and ex vivo studies of increasing complexity showed that FXa I16L , a prototypical zymogen-like FXa species, was highly effective in promoting thrombin generation in hemophilic plasma with or without inhibitors and in hemophilic blood [25, 26, 33]*. As expected from previous biochemical studies, these effects were FVa-dependent.…”
Section: Zymogen-like Fxa For Use In Hemophiliamentioning
confidence: 57%
See 3 more Smart Citations
“…In vitro and ex vivo studies of increasing complexity showed that FXa I16L , a prototypical zymogen-like FXa species, was highly effective in promoting thrombin generation in hemophilic plasma with or without inhibitors and in hemophilic blood [25, 26, 33]*. As expected from previous biochemical studies, these effects were FVa-dependent.…”
Section: Zymogen-like Fxa For Use In Hemophiliamentioning
confidence: 57%
“…AT and TFPI) and, consequently a prolonged half-life in plasma. Interestingly, variants with lowest catalytic activity (the most “zymogen-like”) were the most resistant to inhibitors [24, 25]*. Importantly, since the zymogen-like state has plasticity and is highly dynamic, ligands that engage the enzyme can readily alter its conformational equilibrium.…”
Section: Zymogen-like Fxa-biochemical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In some variations of the method, the tail is cut at 1 to 5 mm from the tip (Maroney et al, 2012;Sambrano, Weiss, Zheng, Huang, & Coughlin, 2001;Tranholm et al, 2003), while in others the tail is amputated at 1 to 4 mm tail diameter (Holmberg, Lauritzen, Tranholm, & Ezban, 2009;Ivanciu & Camire, 2015). The measurable parameters are: bleeding time, measured as cessation of blood flow due to hemostatic plug formation, and total blood loss, measured as the hemoglobin content of blood.…”
Section: Tail Clip Assaymentioning
confidence: 99%